THE IMPLEMENTATION OF KURIKULUM TINGKAT SATUAN PENDIDIKAN IN THE TEACHING OF ENGLISH (A Naturalistic Study in SMK Negeri 2 Surakarta) - SUKIRAN, SUKIRAN (2010)
The objective of the research is to describe the implementation of KTSP in the teaching of English in SMK Negeri 2 Surakarta. The research was carried out from January to April 2010. It is a qualitative research in the form of naturalistic study. The object of the research is the teaching and learning activities of English in SMK Negeri 2 Surakarta. The data were gained from several techniques including non-participant observation, in-depth interview, and document analysis. In analyzing the data, the researcher applied the constant comparative method as a means to derive the theory, i.e, by comparing incidents applicable to each category, integrating categories and their properties, delimitating the theory, and writing theory. The implementation of KTSP has some supporting factors from the syllabus and creativities of teachers' teaching strategy. However, the findings reveal that the implementation of KTSP has some weakening factors, too. Those are from adaption of new curriculum and teachers' character. Dealing with its supporting factors of KTSP, the teachers have rights to arrange their syllabus which are appropriate to the school's need and the condition and the teachers are free to improve and apply any teaching strategy which is the most appropriate and effective for the students to learn. The weakening factors of implementing KTSP is that it needs time to make adaptation since it is as a new curriculum and the teachers' point of views toward KTSP are not easy to change due to their perspective of previous curriculum. Anyhow, there some impacts of the implementation of KTSP to the instructional process in SMK Negeri 2 Surakarta, to the teachers' teaching strategy, and the students' learning intensity. The research finding of this study imply that the implementation of KTSP in teaching English increases the intensity of student to learn. Therefore, it is recommended that (1) the teacher should not only increase their communicative competence, but also have to change their point of view of the KTSP implementation. (2) the school as the educational institution should complete the school with some learning facilities such as sets of multimedia and provide more skillful and competent teachers. (3) the government should take into account the readiness of the lower department and schools in KTSP implementation, and (4) the other researchers develop some dimensions which have not been developed in this research.